2019
DOI: 10.1021/acsomega.9b02262
|View full text |Cite
|
Sign up to set email alerts
|

Recovering Magnesium from Ferronickel Slag by Vacuum Reduction: Thermodynamic Analysis and Experimental Verification

Abstract: The feasibility of recovering magnesium from ferronickel slag by vacuum reduction was evaluated. The thermodynamic calculations indicated that the magnesia in slag can be reduced to gaseous magnesium by Si, FeSi, Al, and C, with the minimum reduction temperatures of 2324, 2530, 1678, and 2580 K at 100 000 Pa, respectively. As the system pressure decreases, the minimum reduction temperatures decline significantly. Si maintains the minimum reduction temperature of 1585–1673 K at the atmospheric pressure of 10–10… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 30 publications
0
7
0
Order By: Relevance
“…Gaseous magnesium resulted from the process since it is the lightest metal present in the raw materials. 97.74 % Mg resulted from the condensation of the gaseous metal [27]. However, this process needs high energy consumption since the condition process is performed at high temperatures and vacuum.…”
Section: Literature Review and Problem Statementmentioning
confidence: 99%
“…Gaseous magnesium resulted from the process since it is the lightest metal present in the raw materials. 97.74 % Mg resulted from the condensation of the gaseous metal [27]. However, this process needs high energy consumption since the condition process is performed at high temperatures and vacuum.…”
Section: Literature Review and Problem Statementmentioning
confidence: 99%
“…These are disodium magnesium silicate [4,7] and sodium chromate [4], which were observed from the roasting process that used sodium compound such as Na 2 O 2 [4] and NaOH [7] as an additive in the roasting process at about 500-600 °C for 1 hour. Moreover, selective extraction of elemental chromium from ferronickel slag via microwave roasting with sodium peroxide addition followed by water leaching yielded 94.21 % soluble chromium, while only 0.06 % by weight of chromium remained in the leach residue [21]. Sodium chromate formation is beneficial since it can be separated by water leaching and prevent environmental pollution.…”
Section: Introductionmentioning
confidence: 99%
“…When the coal-to-slag ratio was maintained at 0.05, these quantities in the metal phase decreased (12% for copper and 20% for cobalt), but recoveries improved to 65% and 90%, depending on the reduction period. The research also revealed that higher temperatures improve reaction kinetics, whereas lower temperatures result in greater quality metal output . In a similar study, Maweja et al also manifested that under 1400 °C temperature carbothermic reduction could exhibit higher metal recovery.…”
Section: Metal Recovery Techniquesmentioning
confidence: 73%